2016
DOI: 10.1007/s12195-016-0467-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial Polarity Determines Individual Cellular and Nuclear Chirality

Abstract: Intrinsic cell chirality has been implicated in the left-right (LR) asymmetry of embryonic development. Impaired cell chirality could lead to severe birth defects in laterality. Previously, we detected cell chirality with an in vitro micropatterning system. Here, we demonstrate for the first time that chirality can be quantified as the coordination of multiaxial polarization of individual cells and nuclei. Using an object labeling, connected component based method, we characterized cell chirality based on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
2
19
1
Order By: Relevance
“…This platform is not intended to fully simulate in vivo environments for LR symmetry breaking, but it provides a simple yet effective system for determining chirality and thereby provides insight into possible regulatory mechanisms of LR asymmetry. We demonstrate that the direction of spontaneous rotation of both selforganized hollow cellular spheroids and individual epithelial cells residing at the interface of two layers of Matrigel is chiral in nature, with a CCW bias that is dependent on functional actin, consistent with the results from 2D ring patterning (16,28,29).…”
Section: Mdck Spheroids Exhibit Coordinated and Persistent Rotation Tsupporting
confidence: 75%
“…This platform is not intended to fully simulate in vivo environments for LR symmetry breaking, but it provides a simple yet effective system for determining chirality and thereby provides insight into possible regulatory mechanisms of LR asymmetry. We demonstrate that the direction of spontaneous rotation of both selforganized hollow cellular spheroids and individual epithelial cells residing at the interface of two layers of Matrigel is chiral in nature, with a CCW bias that is dependent on functional actin, consistent with the results from 2D ring patterning (16,28,29).…”
Section: Mdck Spheroids Exhibit Coordinated and Persistent Rotation Tsupporting
confidence: 75%
“…Patterned cells also demonstrate biases in the alignment of their nuclei and the direction of cell shape elongation. 64,65 Similar nuclear alignment was also observed by Huang et al using an outline etching image segmentation strategy. 60 Interestingly, inhibition of actin polymerization led to the reversal of the CCW chirality of C2C12 mouse myoblasts, supporting the role of the actin cytoskeleton in chirality development.…”
Section: Chirality: Connection Between Molecular and Tissue Chiralitysupporting
confidence: 79%
“…Hametner et al observed the elevation of iron accumulation with age increase in the white matter (WM) 1 . Iron-rich oligodendrocytes, myelin, and microglia were also destroyed in the active MS lesion, increasing the liberated iron, thereby intensifying oxidative damage and neurodegeneration 4 , 48 , 49 . Conversely, considerable reduction of iron and elevation of oxidative stress are found in MS patients 16 , 50 .…”
Section: Cell Biology Of Iron and Its Role In Ms/alsmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a demyelinating disease of the central nervous system (CNS). Its resultant inflammation causes oligodendrocyte degeneration, myelin sheath destruction, and neurodegeneration 1 – 4 . Although the origin of MS is still unknown, genetic predisposition and environmental toxicity activate the immune system against neural cells 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%